Comparison of Morning Training and Evening Training on VO2Max of Futsal Athletes at SMA Negeri 4 Makassar - Awal, Asri; Hamzah, Alimin; Sutriawan, Agus (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to analyze the effect of sports implementation time, namely morning and evening, on the VO2Max of futsal athletes at SMA Negeri 4 Makassar. Formulation of the problem What is the difference in the VO2Max value of futsal athletes at SMA Negeri 4 Makassar who exercise in the morning compared to those who exercise in the evening? This research uses a quantitative approach with experimental methods. The research sample consisted of 10 futsal athletes who exercised in the morning and 10 athletes who exercised in the evening. The data obtained were analyzed using statistical tests with a significance value of P<0.05. The research results showed that the average VO2Max value of athletes who exercised in the morning was 37.8700, while athletes who exercised in the evening had an average VO2Max of 36.2100. The statistical test results showed a P value of 0.00 (P<0.05), which indicated a significant difference between the two groups. The difference in VO2 Max between morning and evening exercise is 1.6600, which shows that morning exercise tends to provide better VO2 Max results than evening exercise. From the results of this research, it can be concluded that the timing of sports has an influence on the VO2 Max of futsal athletes at SMA Negeri 4 Makassar. Exercise done in the morning is more effective in increasing VO2 max capacity compared to exercise in the evening.